Polylactones synthesis by enzymatic ring opening polymerization in flow. (16th September 2021) - Adhami, Wissal; Bakkour, Youssef; Rolando, Christian
Abstract: Polycondensation in batch is the classical way to produce polyesters. However, this method requires harsh conditions to reach high conversions and drive the equilibrium of the reaction forward. In order to produce controlled polymers in a greener way, we worked on the enzymatic ring opening polymerization (e-ROP) of lactones using the CALB lipase immobilized on porous beads (Novozym® 435) as a catalyst and 3-phenyl-1-propanol (PP) as initiator in a flow tubular reactor made of fluorinated ethylene propylene (FEP) tubing with i.d  = 1.55 mm. In a short residence time of 214 s ε-caprolactone (CL) was fully polymerized (conv = 100 %) with a fair dispersity ( Đ  = 1.30). Polymerization of δ-valerolactone (VL) (conv = 93 %, Đ  = 1.27) as well as copolymerization of CL and VL mixtures (conv up to 88 %, Đ  = 1.24) behaved similarly. By alternating the lactones, a block-polymer was obtained. As expected, primary alcohols were more efficient than secondary ones for initiating the e-ROP of lactones. Very interestingly, using cholesterol as initiator induced the formation of cyclic polylactones only. In addition, we showed the importance of the residence time as at a long time the formed polymer was depolymerized by the enzyme. We demonstrated also that the enzyme may be reused more than ten times with maintaining its high efficiency. The whole study shows that the use of tubular reactor for performing e-ROP improves its control as shown by the low Đ values and decreases the residence time needed to reach high conversions compared to similar reactions in batch. Graphical abstract: Immobilized enzymes in FEP tubing for lactone e-ROP in flow. Image 1 Highlights: Controlled enzymatic ring opening polymerization of ε −capro- and δ−valero-lactones in flow catalyzed by N435® beads. FEP tubing of a small diameter i.d  = 1.55 mm improves polymerization control. Residence time governs the balance between polymerization and degradation by enzyme. Cholesterol, not acting as an initiator, strongly favors the formation of cyclic polylactones.